Grime and punishment: job insecurity and wage arrears in the Russian Federation - Lehmann, Hartmut (Discussion paper series, 1999)
Using information from two complementary household survey data sets, we show that the dominant form of labor market adjustment in the Russian transition process has been the delayed receipt of wages. More than half the workforce is experiencing some form of disruption to their pay. Wage arrears are found across the private, state and budgetary sector. Workers in the metropolitan center are less affected by delayed and incomplete wage payments than workers in the provinces. There is less evidence that individual characteristics contribute much toward the incidence of wage arrears, but the persistence of arrears is concentrated on a subset of the working population. We show that workers can only exercise the exit option of a job quit from a firm not paying wages in full or on time if the outside labor market is sufficiently dynamic.